SMART SPECIALIZATION IN THE POSTULATES OF ECONOMIC SCHOOLS: THEORETICAL DISCOURSE - Voznyak , H.V. (The actual problems of regional economy development, 2021)
The article reviews modern theories of economic development of territories, the expediency of which will allow to reduce the gap between the practical orientation of smart specialization and its theoretically sound concept. The aim of the article is to study the evolution of theories in the postulates of economic schools, which form the theoretical basis of smart specialization of regions. The application of methods of logical generalization, analysis and historical approach allowed to assert that the theoretical basis of smart specialization is formed by ideas of endogenous growth theory, theoretical postulates of uneven development, separate positions of creative class theory, information society, a number of provisions of collective action theory. It is found that the formation of the theoretical concept of smart specialization of regions at the present stage is associated with the actualization of the theory of endogenous growth, the key idea of ​​which is based on internal factors and mechanisms of technological progress, which together can ensure self-development and self-reproduction systems. A balanced combination of government intervention, protectionism and strategic investment are the determining determinants of the economic progress of the proponents of the theory of "economic nationalism", which convincingly proves that only through industrialization can prosperity be achieved. It is argued that every year the traditional factors of economic growth lose their weight, while the creative class becomes more important, and openness and sharing become the latest principles of socio-economic systems. The common expression of the analyzed concepts is the development of relationships between stakeholders, the development and strengthening of multilateral partnerships, communication with external networks, the formation and promotion of the uniqueness of the region. Such dominants, the synergy of which will guarantee entrepreneurial opening and competitive advantage of the region, become especially relevant in the current conditions. The study indicates the need to apply the key provisions of these theoretical concepts in substantiating the theoretical and methodological core of smart specialization.